(untitled) (Comparatismi, 2025)
The article explores the dialogue between Heidegger and Hölderlin, showing how poetry becomes, for the German philosopher, the original site of temporal experience. In Hölderlin’s word, Heidegger recognizes a saying that transforms the interpreter, dissolving the distance between writer and thinker. Poetry, as authentic time, precedes all logic: it is the dwelling where language brings the world into being and thought rediscovers its “other beginning.”